Anti-inflammatory activity of ethanol extract and fractions from Couroupita guianensis Aublet leaves. - Boylan, Fabio (My University, 2013)
Abstract Ethnopharmacological relevance Couroupita guianensis Aublet, ‘macacarecuia’, ‘abricó-de-macaco’, ‘castanha-de-macaco’ and ‘amêndoa-dos-andes’, is found in tropical regions and is widely used in the treatment of tumors, pain, and inflammatory processes. Aim of the study Ethanol extract and hexane and ethyl acetate fractions were evaluated in models of inflammatory pain (formalin-induced licking) and acute inflammation (carrageenan-induced peritonitis). Materials and methods Ethanol extract, hexane and ethyl acetate fractions (10, 30 or 100 mg/kg, p.o.) and the reference drugs dexamethasone (5 mg/kg), morphine (5 mg/kg, s.c.), and acetylsalicylic acid (100 mg/kg, p.o.) were tested in formalin-induced licking response and carrageenan-induced peritonitis. Results All three doses from Couroupita guianensis fractions significantly reduced the time that the animal spent licking the formalin-injected paw in first and second phases. However, only higher doses (30 and 100 mg/kg) were able to inhibit the leukocyte migration into the peritoneal cavity after carrageenan injection. In this model, the 100 mg/kg dose almost abolished the cell migration. It was also observed that protein concentration resulted from extravasation to the peritoneum and nitric oxide (NO) productions were significantly reduced. Cytokines production was differently affected by the treatment. TNF-α production was reduced after ethanol extract and ethyl acetate fraction pre-treatment whereas hexane fraction had effect only with 100 mg/kg dose. IL-1β production was inhibited only after hexane fraction pre-treatment. The inhibitory effect observed was not due to a direct cytotoxic effect on cells nor to a NO-scavenger activity. The effect was due to a direct inhibition on NO production by the cells. Conclusions The results show that Couroupita guianensis fractions have anti-inflammatory effect, partly due to a reduction on cell migration and a inhibition on cytokines and inflammatory mediators production.
PUBLISHED
Keywords: Anti-inflammatory activity; Cytokine; Nitric oxide; Lecythidaceae; Couroupita guianensis; Immunology, Inflammation & Infection; International Development